Analisis Pengaruh Kualitas Produk dan Promosi Penjualan (Sales Promotion) Terhadap Repeat Order Konsumen Produk Skincare Merek Garnier (Studi Kasus Bravo Supermarket Tulungagung) - Mochammad Annas; Nafik Umurul Hadi (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
The purpose of this study is to identify product quality improvement and promotion for repeat orders. Nowadays, more and more SkinCare products are emerging from various countries around the world, which is detrimental to the SkinCare industry. Bravo Swalayan Tulungagung is now the most contemporary supermarket in Tulungagung. The population in this study were 1,192 consumers of Garnier brand skincare products at Bravo Supermarket Tulungagung with a sample of 93. This research model uses a formative model. Partial Least Squares (PLS) data analysis technique using two correction models, outer and inner models, derived from Validity Test, Reliability Test. Based on the analysis results, it is possible to determine the unique validity of each indicator. When the reliability of the composition corresponds to a given variable, then the composition is reliable because the loading threshold is greater than 0.70. The coefficient of determination states that product quality and marketing efforts have a significant impact on repeat business, with a 57.3% correlation between the two factors and 42.7% not accounted for in the model.